Conflict Resolution Learning Model In Multicultural-Religious Education At Madrasah Aliyah Negeri (MAN) 1 East Lampung - Nuryanto Nuryanto (IAI Ma'arif NUMetro Lampung, 2018)
The main objectives of this study are: 1) to understand the conflicting picture, especially the students' conflict in the Madrasah environment; 2) to know the description of madrasah programs related to conflict resolution; 3) to know the distinctive concept of Multicultural-Religious Education; 4) to know the implementation of conflict resolution learning in Multicultural-Religious Education in Madrasahs; and 5) to know the impact of conflict resolution learning in Multicultural-Religious Education students in Madrasah Aliyah Negeri (MAN) 1 East Lampung. This type of research is qualitative descriptive. Data collection techniques use documentation and interviews. The results of this study indicate that learning conflict resolution in MAN 1 East Lampung performed by instilling the values of multicultural education based on the principle of transparency (openness), tolerance (tolerance), unity in diversity (unity in diversity), and Islam rahmatan lil'amalin. Keywords: Conflict Resolution, Multicultural-Religious Education, Madrasah Aliyah Negeri (MAN)